(untitled) (Ozone Therapy Global Journal, 2022)
Introduction: Tooth whitening has been increasingly sought after by patients of all ages who aim to improve the aesthetics of their teeth in terms of coloration. Case report: Male patient goes to the dental office in order to improve their dental aesthetics through whitening. Tooth color and sensitivity were evaluated before and after the application of gaseous ozone solution. Ozone was applied by insufflation in an individual tray previously made in 4 cycles of 5 min at a concentration of 80 µg/ml. Conclusion: The results of this study confirmed the effectiveness of ozone as a tooth whitening agent. It was found to be a quick and effective procedure, painless and without adverse effects for the patient